The Effects of Combining Prenatal Gentle Yoga with Lavender Aromatherapy on Lower Back Pain and Sleep Quality in Third-Trimester Pregnant Women - Aswitami, Ni Gusti Ayu Pramita; Udayani, Ni Putu Mirah Yunita; Maryani, Ni Made Septiari (Jurnal Bidan Cerdas, 2025)
Introduction: During the third-trimester pregnancy, 70% of pregnant women experience back pain and 64% sleep problems. Pharmacological approaches may increase prenatal abnormalities with adverse consequences for the fetus due to side effects. Therefore, non-pharmacological techniques are attracting lot of interest and attention from pregnant women to overcome these discomforts. Purpose: To determine effects of combining prenatal gentle yoga with lavender aromatherapy on lower back pain and sleep quality in third-trimester pregnant women. Methods: The design was Quasy-experimental of Pre-Posttest with Non-equivalent Control Groups. The study was conducted from February to August 2023 at Puskesmas Mengwi I, Badung Regency, Bali. 44 third-trimester pregnant women were selected by a simple random sampling technique and assigned to two groups: control and intervention. Results: Low back pain in the control group was higher than the intervention group (p-value 0.000). Sleep quality in the control group was lower than the intervention group (p-value 0.000). In the intervention group, there was a significant difference in low back pain before and after the study (p-value = 0.000), as well as in sleep quality before and after the study (p-value = 0.000). Conclusion: The combination yoga with lavender aromatherapy can improve the scale of lower back pain and better sleep quality for pregnant women in the third trimester.